2021
DOI: 10.1002/2688-8319.12055
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation activity of harbour porpoises, Phocoena phocoena, shows seasonal artificial reef attraction despite elevated noise levels close to oil and gas platforms

Abstract: 1. Harbour porpoises frequently alter their behaviour in response to underwater sound from shipping, seismic surveys, drilling and marine renewables. Less well understood is the response of porpoises to sounds emitted from oil and gas (O&G) platforms during routine operations. 2. The responses are not easily predicted as platforms can act simultaneously and to varying degree as a source of disturbance through noise and attraction through an artificial reef effect with increased prey abundance and diversity. 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 48 publications
4
13
1
Order By: Relevance
“…To date, just one study has demonstrated that harbour porpoises are locally attracted to O&G structures. In this case, within the Danish sector of the North Sea, porpoise echolocation activity was up to twofold higher within 800m of an operational O&G platform compared to reference sites (Clausen et al, 2021). As demonstrated in earlier work from a jack-up barge around a gas platform in the German sector of the North Sea, porpoise echolocation activity was also highest during the night (Todd et al, 2009).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…To date, just one study has demonstrated that harbour porpoises are locally attracted to O&G structures. In this case, within the Danish sector of the North Sea, porpoise echolocation activity was up to twofold higher within 800m of an operational O&G platform compared to reference sites (Clausen et al, 2021). As demonstrated in earlier work from a jack-up barge around a gas platform in the German sector of the North Sea, porpoise echolocation activity was also highest during the night (Todd et al, 2009).…”
Section: Introductionsupporting
confidence: 62%
“…It is recognised that marine mammals may be attracted to artificial offshore structures in certain situations (Russell et al, 2014;Clausen et al, 2021), but the generality of these findings is less clear. This is partly because studies have focused on a limited number of the many designs of structure currently installed offshore, but also because research has been conducted only in a few ecological regions.…”
Section: Introductionmentioning
confidence: 99%
“…echolocation around offshore O&G installations may indicate foraging behaviour, particularly at night (Clausen et al, 2021;Todd et al, 2009), and were closer to the installations than at control sites further away (Clausen et al, 2021). Satellite tracking of pinnipeds (harbour Phoca vitulina and grey seals Halichoerus grypus)…”
Section: Marine Megafaunamentioning
confidence: 98%
“…Attraction included infrequent visits over a 6‐week period, to high residency, potentially for feeding (Thomson et al, 2021), with feeding observed at offshore platforms in the Arabian Gulf (Robinson et al, 2013). Passive acoustic monitoring detection of harbour porpoise ( Phocoena phocoena ) echolocation around offshore O&G installations may indicate foraging behaviour, particularly at night (Clausen et al, 2021; Todd et al, 2009), and were closer to the installations than at control sites further away (Clausen et al, 2021). Satellite tracking of pinnipeds (harbour Phoca vitulina and grey seals Halichoerus grypus ) shows that some individuals can spend prolonged periods at O&G infrastructure for foraging (Russell et al, 2014).…”
Section: How Does Oandg Infrastructure Influence the Movement Of Mobi...mentioning
confidence: 99%
See 1 more Smart Citation